Systemic approach to knowledge and skills management in the context of education administration - Firsts, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Much has been written on the significance of knowledge management, the challenges facing organizations, and the relevant human resource management activities involved in assuring the acquisition and transfer of knowledge. Higher education plays an important role in preparing students to assume the knowledge management and human resource roles so necessary to organizations. The authors examined the relationship between knowledge management, human resource management, and typical knowledge learning goals of an accredited medical education program. The work is based on the relationship between knowledge management, human resource management and competence development process.